Odpowiedzi

Najlepsza Odpowiedź!
2010-02-13T12:52:25+01:00
A) 3(x+3)=2(x+4)+x+1
3x+9=2x+8+x+1
3x-2x-x=8+1-9
0x=0

b) 4(x-2)-2(x-4)=5 (x+1)-3x
4x-8-2x+8=5x+5-3x
4x-2x-5x+3x=5+8-8
0x=5

c) 7(y+3)=5y+2+2y
7y+21=5y+2+2y
7y-5y-2y=2-21
0y=-19

d) y/2 +1/3 = 7/6 /*6
3y+2=7
3y=7-2
3y=5/:3
y=5/3

e) 8x- 0,2 = 8x - 0,1
8x-8x=-0,1+0,2
0x=0,1
2010-02-13T12:54:19+01:00
A)3x+9=2x+8+x+1
3x-2x-x=8+1-9
0=0
b)4x-8-2x+8=5x+5-3x
4x-2x-5x+3x=5+8-8
0=5 |÷(-3)
x=-5/3
c)7y+21=5y+2+2y
7y-5y-2y=2-21
0=-19
d)y/2=7/6-1/3
y/2=7/6-2/6
y/2=5/6 |×2
y=5/3
e)8x-8x=-o,1+0,2
0=0.1

2010-02-13T14:08:51+01:00
A) 3(x+3)=2(x+4)+x+1
3x+9=2x+8+x+1
3x-2x-x=8+1-9
0x=0

b) 4(x-2)-2(x-4)=5 (x+1)-3x
4x-8-2x+8=5x+5-3x
4x-2x-5x+3x=5+8-8
0x=5

c) 7(y+3)=5y+2+2y
7y+21=5y+2+2y
7y-5y-2y=2-21
0y=-19

d) y/2 +1/3 = 7/6 /*6
3y+2=7
3y=7-2
3y=5/:3
y=5/3

e) 8x- 0,2 = 8x - 0,1
8x-8x=-0,1+0,2
0x=0,1